(untitled) (Journal of the College of Basic Education, 2022)
Richard Wright (1908- 1960), an African American author, has grown up in the American South at a time when the American society has witnessed deep division, for together with the Whites vs. Blacks conflict there has been The Blacks vs. Blacks tension likewise, and violence has formed the dominant behavior between the conflicting groups. Wright’s autobiographical novel, Black Boy, shows how he has been reared by a mother who believes that violence is the only effective strategy to protect her son from their violent environment. The misery and hardships the mother, Ella Wright, has undergone in her larger society as well as with her family and separated husband, have led her to adopt this strategy. She uses violence to teach her son the priority of family, religion, and beyond everything else she teaches him violence itself as a means of self-protection. Albeit this strategy affects the mother-son relationship negatively on the part of the son at the beginning, the son’s intellectual maturity minimizes its significance, and he gradually starts to generate sympathy and show deep understanding towards his mother. The article discusses Wright’s mother use of violence as a method for bringing up her son, Richard Wright in his autobiography, Black Boy. It also examines the impact of this method upon Richard’s relationship with his mother and how he perceives her maternal role. Finally, the conclusion sums up the main findings of the article.